In search of a scientific basis for teacher preparation - Gable*, Robert A (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
Statement of the Problem: There is growing pressure on school personnel to rely on the use of evidence-based teaching practices. Unfortunately, research indicates that few beginning teachers engage in evidence-based practices or do so across time. Replacement of the hodgepodge of flawed and ineffective strategies with those that are based on strong empirical support poses major challenges.Research Topic: A major challenge exists with regard to the reform of teacher preparation programs so that they reflect what is known about the science of teacher education. In addition, once students graduate, ways must be found to promote the use of evidence-based practices with fidelity.General findings: First, based on a review of the literature, it appears that teacher educators should examine critically both the university curriculum and teaching practices to ensure they have strong empirical support. Second, the need exists to alignment innovative university instruction with highly structured field-based experiences. Third, it is important to provide beginning teachers a systematic ‘induction’ into the workplace to minimum the disconnect between university and K-12 classrooms. Finally, there is mounting evidence that coaching represents a powerful tool for facilitating teacher implementation of evidence-based practices with fidelity.Received: 18th August 2016; Revised: 26th October 2016; Accepted: 31st October 2016